2020
DOI: 10.21203/rs.2.12665/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of mean platelet volume in hypertriglyceridemia-induced acute pancreatitis during pregnancy

Abstract: Background: Hypertriglyceridemia-induced acute pancreatitis during pregnancy (HTG-APP) is a rare but severe disease with high maternal-fetal mortality risk, which constitutes a systemic inflammatory process accompanied by thrombosis and bleeding disorders. However, the role of mean platelet volume (MPV) in HTG-APP remains unclear.Methods: In the retrospective study, we collected 45 patients with HTG-APP as the HTG-APP group and 49 pregnant females with hypertriglyceridemia as the control group. MPV and other r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The rates of local complications and organ failure increase significantly and dose-dependently with the level of triglycerides (8). The trend of HTG-induced AP has been observed to increase with the gestational age and number of pregnancies (9). This disease constitutes a systemic inflammatory process accompanied by thrombosis, and bleeding disorders result in multiple organ dysfunction and disseminated intravascular coagulation (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of local complications and organ failure increase significantly and dose-dependently with the level of triglycerides (8). The trend of HTG-induced AP has been observed to increase with the gestational age and number of pregnancies (9). This disease constitutes a systemic inflammatory process accompanied by thrombosis, and bleeding disorders result in multiple organ dysfunction and disseminated intravascular coagulation (9).…”
Section: Discussionmentioning
confidence: 99%
“…The trend of HTG-induced AP has been observed to increase with the gestational age and number of pregnancies (9). This disease constitutes a systemic inflammatory process accompanied by thrombosis, and bleeding disorders result in multiple organ dysfunction and disseminated intravascular coagulation (9). Yang et al showed that HTGinduced AP along with a delayed diagnosis was related to a 66.7% fetal loss (10).…”
Section: Discussionmentioning
confidence: 99%